Prognostic Analysis of Limited Resection Versus Lobectomy in Stage IA Small Cell Lung Cancer Patients Based on the Surveillance, Epidemiology, and End Results Registry Database - Gu, Chang; Huang, Zhenyu; Dai, Chenyang; Wang, Yiting; Ren, Yijiu; She, Yunlang; Su, Hang; Chen, Chang (Frontiers in Genetics, 2018)
Objective: The prognostic analysis of limited resection vs. lobectomy in stage IA small cell lung cancer (SCLC) remains scarce. Methods: Using the Surveillance, Epidemiology, and End Results registry (SEER) database, we identified patients who were diagnosed with pathological stage IA (T1a/bN0M0) SCLC from 2004 to 2013. The overall survival (OS) and lung cancer-specific survival (LCSS) rates of patients with different treatment schemes were compared in stratification analyses. Univariable and multivariable analyses were also performed to identify the significant predictors of OS and LCSS. Results: In total, we extracted 491 pathological stage IA SCLC patients, 106 (21.6%) of whom received lobectomy, 70 (14.3%) received sublobar resection and 315 (64.1%) received non-surgical treatment, respectively. There were significant differences among the groups based on different treatment schemes in OS (log-rank p < 0.0001) and LCSS (log-rank p < 0.0001). Furthermore, in subgroup analyses, we did not identify any differences between sublober resection group and lobectomy group in OS (log-rank p = 0.14) or LCSS (log-rank p = 0.4565). Patients with four or more lymph node dissection had better prognosis. Multivariable analyses revealed age, laterality, tumor location, and N number were still significant predictors of OS, whereas age, tumor location, and N number were significant predictors of LCSS. Conclusion: Surgery is an important component of multidisciplinary treatment for stage IA SCLC patients and sublober resection is not inferior to lobectomy for the specific patients.